Diagnosis and treatment-related issues of autoimmune epilepsy - O. S. Shilkina; E. E. Timechko; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния, 2023)
Due to elevated frequency of autoimmune epilepsy cases, the issues related to reliable clinical and laboratory-instrumental criteria for establishing the disease etiology become relevant. Differentiated assessment of autoantibody markers allows to choose the most effective tactics for managing patients. The article presents the criteria for assessing autoimmune epilepsy as well as diagnostic scales, features related to clinical picture and response to therapy based on the type of synthesized autoantibodies. Therapeutic lines and targets for immunomodulatory and antiepileptic drugs used in autoimmune epilepsy are detailed, the knowledge of which along with clinical and laboratory data collectively allow to determine effective and safe therapy algorithm.